THE GIERSTAD KILN: A COMBINED HOT AND COLD SMOKING KILN - GJERSTAD, DAG (Fishery Technology, 2017)
A combined hot and cold smoking kiln has been constructed for use at Lake Turkana, Kenya. Used for cold smoking, the kiln's main advantages over the traditional kilns used in this area are its greater smoking capacity and lower firewood consumption. Having the option of using the same smoke house for cold and hot smoking reduces the total construction costs for an operator producing both types of smoke cured product. The hot smoking process was found to require markedly less firewood than cold Â smoking, a fact of considerable importance in desert or semi-desert areas with sparse vegetation.